Collaborative Learning Model Based On Peer Tutoring Class Wide: Improving Students Critical Thinking In Biology Learning - Nasrul Hakim; Aprizal Lukman; Dwi kurnia Hayati; Yudiyanto Yudiyanto; Tika Mayang Sari; Hifni Septina Carolina; Asih Dewi; Tri Andri Setiawan (International Journal of Education, Information Technology, and Others, 2020)
This research aimed to identify the effect of learning experiences through peer tutoring on students' critical thinking skills in biology learning. Then the specific target to be achieved from this study is a learning innovation that has a rapid effect on improving students' critical thinking skills in biology learning in high school students in Jambi City. The research method uses quasi-experimental research design. The procedure used was the pretest and posttest nonequivalent control group design experimental procedure. Hypothesis testing results that T count ≥ T table (2.12 ≥1.69) with a significance level of 0.05. It can be concluded that Ho was rejected and Ha was accepted. The achievement of critical thinking skills on experimental class was higher with a percentage of 58.78% compared to the control class with a percentage of 55.26%. The conclusion from this research is that there is a significant effect on implementation of collaborative learning models using the Class wide Peer Tutoring strategy toward students' critical thinking skills.